Gazing and Typing Activities during Translation: A Comparative Study of Translation Units of Professional and Student Translators - Carl, Michael; Kay, Martin (Meta, 2011)
The paper investigates the notion of Translation Units (TUs) from a cognitive angle. A TU is defined as the translator’s focus of attention at a time. Since attention can be directed towards source text (ST) understanding and/or target text (TT) production, we analyze the activity data of the translators’ eye movements and keystrokes. We describe methods to detect patterns of keystrokes (production units) and patterns of gaze fixations on the source text (fixation units) and compare translation performance of student and professional translators. Based on 24 translations from English into Danish of a 160 word text we find major differences between students and professionals: Experienced professional translators are better able to divide their attention in parallel on ST reading (comprehension) and TT production, while students operate more in an alternating mode where they either read the ST or write the TT. In contrast to what is frequently expected, our data reveals that TUs are rather coarse units as compared to the notion of ‘translation atom,’ which coincide only partially with linguistic units.